Ethnic variation in the live birth rate and perinatal outcomes following frozen embryo transfer: an analysis of the HFEA database from 2000 to 2016. (27th May 2022) - Sharpe, Abigail; Mascarenhas, Mariano; Balen, Adam
Abstract: The literature suggests that ethnicity affects live birth rate (LBR) and preterm birth (PTB) rate after fresh but not frozen embryo transfer (FET). We analysed 64, 530 FET cycles from 2000 to 2016 using the Human Fertilisation and Embryology Authority (HFEA) database. Ethnicity was recorded for 43, 735 as White British, 3, 034 as Indian, 1, 946 as Pakistani, 1, 400 as Black African, 1, 090 as White Irish, 520 as Chinese, 319 as Bangladeshi and 277 as Black Caribbean women. The LBR per FET when compared with White British women (26.1%) was significantly reduced in women of White Irish (23.4%; adjusted Odds Ratio (aOR) 0.85, 95% CI 0.73 to 1.00), Indian (25.2%; aOR 0.95, 95% CI 0.91 to 0.99), Bangladeshi (21.1%; aOR 0.87, 95% CI 0.79 to 0.95) and Pakistani (25.7%; aOR 0.97, 95% CI 0.94 to 0.99) ethnicities. The PTB rate, when compared with White British women (8.4%) was significantly higher for women of Indian (11.1%; aOR 1.38, 95% CI 1.06 to 1.79), Pakistani (11.8%; aOR 1.49, 95% CI 1.09 to 2.03) and White Irish (12.3%; aOR 1.55, 95% CI 1.01 to 2.38) ethnicities. This study suggests that FET outcomes are influenced by ethnicity.